Augmentative and Alternative Communication and digital participation - Wahl, Michael; Weiland, Katharina (Frontiers in Communication, 2023)
Communication is a basic need for all people to fully participate in life. Persons with disabilities may face particular challenges in developing their communication skills and using them appropriately in different situations. Augmentative and Alternative Communication (AAC) tools and methods can assist individuals in this process. Increasing digitization has changed the way everyone communicates, and this offers opportunities for persons using AAC. This paper briefly outlines what has been achieved in terms of digitalization in AAC. The need for full, adapted access to technology is highlighted and research desiderata are identified.